Web services para consultas de estados de cuentas en línea de los socios de la cooperativa de ahorro y crédito 9 de octubre ltda - Tenorio Toapanta, Edison Bolívar (2016)
The Cooperative de “Ahorro y Crédito 9 de Octubre Ltda.”, is born at the initiative of promoting jobs for its habitants through loans granted by the institution, its objective is to deliver effective solutions to micro-financial system, with new proposals founded on responsibility and Services. Currently the Cooperative carries information about the statement of partners internally and centrally, and not accessible outside the institution. In recent years new information technologies open a world of possibilities for the development of applications that facilitate and improve Internet banking Services. In the financial sector is given a big boom to the dynamic Web sites for its many advantages, accessibility and security in the information entered by the customer.